2015
DOI: 10.4085/1052-6050-50.2.13
|View full text |Cite
|
Sign up to set email alerts
|

Proximal Rectus Femoris Avulsion: Ultrasonic Diagnosis and Nonoperative Management

Abstract: Objective: To present a case of ultrasonic diagnosis and nonoperative management of a complete proximal rectus femoris avulsion in a National Collegiate Athletic Association Division 1 soccer goalkeeper.Background: While delivering a goal kick, a previously uninjured 24-year-old collegiate soccer goalkeeper had the sudden onset of right anterior thigh pain. He underwent rehabilitation with rapid resolution of his presenting pain but frequent intermittent recurrence of anterior thigh pain. After he was provided… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
46
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(51 citation statements)
references
References 9 publications
0
46
0
2
Order By: Relevance
“…20 The treatment of any PRF injury can be nonoperative in sedentary people and in physically low-demand athletes. 4,8 As activity levels vary between different sports, even top-level American football players have been treated without surgery with good results. 5 However, in the study of Gamradt et al, 5 only avulsions at the anterior inferior iliac spine were shown, without mentioning retraction of the reflected head.…”
Section: Discussionmentioning
confidence: 99%
“…20 The treatment of any PRF injury can be nonoperative in sedentary people and in physically low-demand athletes. 4,8 As activity levels vary between different sports, even top-level American football players have been treated without surgery with good results. 5 However, in the study of Gamradt et al, 5 only avulsions at the anterior inferior iliac spine were shown, without mentioning retraction of the reflected head.…”
Section: Discussionmentioning
confidence: 99%
“…This procedure is not indicated for nondisplaced or minimally displaced avulsions, musculotendinous tears with minimal or no muscular retraction, and chronic tears in low-demand elderly patients without pain who have an acceptable functional level because of excellent results with conservative management. 4,9,10 It is the opinion of the senior author (C.P-G.) that patients in whom nonoperative treatments fail (continued pain or weakness) for more than 3 months may also be considered for surgical treatment. Indications and contraindications are summarized in Table 1.…”
Section: Indicationsmentioning
confidence: 99%
“…Eighteen percent of the NFL players did suffer a recurrence of symptoms however. A case report involving a similar proximal rectus femoris injury (direct head torn and indirect head avulsed) in a collegiate Division 1 soccer player described a more than 20‐week nonsurgical rehabilitation program before a return to full play [9]. In this report and others in the literature, there are scant details about the nonsurgical rehabilitation program for this kind of injury.…”
Section: Discussionmentioning
confidence: 84%
“…These kinds of injuries are rare, representing only 0.5% of all reported hip and pelvic injuries [8]. To our knowledge, there are significantly fewer numbers of documented cases involving both direct and indirect head avulsions at the musculotendinous junction [4,9]. Such injury statistics could change with the increasing number of players involved socially and recreationally in other sports in addition to kickball, such as foot volley, sepak takraw, futsal, hacky sack, footbag net, footgolf, kegball, and human foosball.…”
Section: Discussionmentioning
confidence: 99%